Impact of progesterone on innate immunity and cell death after influenza A virus H1N1 2009 infection of lung and placental cells in vitro - Li, Miranda; Li, Amanda; Huang, Hazel; Munson, Jeff; Obadan, Adebimpe; Fuller, Deborah H.; Adams Waldorf, Kristina M. (Frontiers in Virology, 2022)
The influenza A virus (IAV) 2009 H1N1 pandemic was associated with an increased risk of maternal mortality, preterm birth, and stillbirth. The underlying mechanism for severe maternal lung disease and stillbirth is incompletely understood, but IAV infection is known to activate innate immunity triggering the release of cytokines. Elucidating the impact of progesterone (P4), a key hormone elevated in pregnancy, on the innate immune and inflammatory response to IAV infection is a critical step in understanding the pathogenesis of adverse maternal-fetal outcomes. IAV H1N1 pdm/09 was used to infect cell lines Calu-3 (lung adenoma) and ACH-3P (extravillous trophoblast) with or without P4 (100 nM) at multiplicity of infections (MOI) 0, 0.5, and 3. Cells were harvested at 24 and 48 hours post infection (hpi) and analyzed for cytopathic effects (CPE), replicating virus (TCID50), cytotoxicity (Lactate Dehydrogenase (LDH) assay), and NLRP3 inflammasome activation (caspase-1 activity, fluorometric assay). Activation of antiviral innate immunity was quantified (RT-qPCR, Luminex) by measuring biomarker gene and protein expression of innate immune activation (ifit1, ifnb), inflammation (il6), interferon signaling (mxa), chemokines (IL-8, IL-10). Both Calu-3 and ACH-3P were highly permissible to IAV infection at each timepoint as demonstrated by CPE and recovery of replicating virus. In Calu-3, progesterone treatment was associated with a significant increase in cytotoxicity, increased gene expression of il6, and increased protein expression of IFN-, IL-6, and IL-18. Conversely, in ACH-3P, progesterone treatment was associated with significantly suppressed cytotoxicity, decreased gene expression of ifnb, il6 and il1b, and increased protein expression of IFN- and IL-6. In both cell lines, caspase-1 activity was significantly decreased after progesterone treatment, indicating NLRP3 inflammasome activation was not underlying the higher cell death in Calu-3. In summary, these data provide evidence that progesterone plays a dual role by ameliorating viral infection in the placenta but exacerbating influenza A virus-associated injury in the lung through nongenomic modulation of the innate immune response.